Necessity of law - Yeoman, Frank (My University, 1898)
Introduction: The term law is not well chosen, because of its broad meaning, serving as it does alike the theologist, the physicist, the chemist the economist or other natural philosopher as well as the compiler and interpreter of the rules of society. It is from the stand point of this latter class we shall consider the term in this theses. Black stone, whose opinion is quite universally accepted, refers to the law as the science which “distinguishes the criterions of right and wrong; which teaches to establish the one, prevent, punish, or redress the other; which employs in its theory the noblest faculties of the soul, and exerts in its practice the cardinal virtues of the heart; a science which is universal in extent, accommodated to each individual, yet comprehending the whole community; a science in which the greatest powers of understanding we applied to the largest number of facts; a science to which all mankind resort in their hours of trouble; which is the asylum of innocence accused, of confidence betrayed, of promises broken, of property invaded, of reputation slandered, of liberty assailed, or domestic relations violated, and of life itself endangered.” Such is its wide reaching influence and power that its adherents command the public sway. The decrees and decisions of our judges are bound to be carried into execution, for they are supported by the whole state. They constitute the public force.
Citation: Yeoman, Frank. Necessity of law. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Law; Theologist; Physicist; Chemist; Economist; Black Stone; Theses; Manuscripts (documents)